In quest of optimal drug-supported and targeted bone regeneration in the cranio facial area: a review of techniques and methods. (2nd October 2015) - Lucaciu, Ondine; Crisan, Bogdan; Crisan, Liana; Baciut, Mihaela; Soritau, Olga; Bran, Simion; Biris, Alexandru Radu; Hurubeanu, Lucia; Hedesiu, Mihaela; Vacaras, Sergiu; Kretschmer, Winfried; Dirzu, Noemi; et al.
Abstract: Craniofacial bone structures are frequently and extensively affected by trauma, tumors, bone infections and diseases, age-related degeneration and atrophy, as well as congenital malformations and developmental anomalies. Consequently, severe encumbrances are imposed on both patients and healthcare systems due to the complex and lengthy treatment duration. The search for alternative methods to bone transplantation, grafting and the use of homologous or heterologous bone thus responds to one of the most significant problems in human medicine. This review focuses on the current consensus of bone-tissue engineering in the craniofacial area with emphasis on drug-induced stem cell differentiation and induced bone regeneration.